The Connection between Individuals' Knowledge Levels and Their Interest in Using IUD Contraceptive Devices - Musliani Musliani; Rosyidah Alfitri; Rani Safitri (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Population policy in Indonesia represents a key government effort to regulate and control population growth. One of the most significant strategies in managing population growth is Family Planning, which helps reduce the rate of fertility and support healthier families. Among the various contraceptive methods, the IUD (Intrauterine Device) is a non-hormonal option that is commonly used by Fertile Age Couples (FACs). The goal of this study was to explore the relationship between the level of knowledge and the interest in the IUD contraceptive method among couples in the Puskesmas Pugaan area. This research employed an analytical approach using a cross-sectional design. The population for this study included all fertile couples in the Pugaan Health Center area. A purposive sampling technique was applied, selecting a sample of 20 participants. Data were collected through questionnaires, and the data were analyzed using the chi-square test with the SPSS version 25 software. The study found that 12 participants (60%) had good knowledge of IUDs, 5 participants (25%) had sufficient knowledge, and 3 participants (15%) had poor knowledge. Regarding interest in using IUDs, 16 participants (80%) expressed an interest, while 4 participants (20%) were not interested in using the IUD. The chi-square statistical test yielded a P value of 0.000 (P < 0.05), indicating a statistically significant relationship between knowledge level and interest in the IUD contraceptive method. In conclusion, this study demonstrates that there is a significant relationship between the level of knowledge and the interest in using IUD contraception at Puskesmas Pugaan. These findings suggest that improving the knowledge of couples about contraceptive methods like the IUD may play a crucial role in increasing interest and usage rates, contributing to more effective population control efforts